Regulating knowledge in an entangled world
1 online resource (xii, 242 pages)
Keywords: "Regulating Knowledge in an Entangled World uses case studies from the sixteenth to the eighteenth centuries to study knowledge transfer in early modern knowledge societies. By bringing together historians from intellectual history, economic history, book history, the history of science, religion, art and material culture, this volume is useful for students and scholars interested in early modern knowledge societies and changing patterns of knowledge transfer"--